Reticulated python Malayopython reticulatus (Schneider, 1801): rescue, recovery and recent sightings from Great Nicobar Island-a conservation approach - Rajeshkumar, S.; Raghunathan, C; Chandra, Kailash (Ecoprint: An International Journal of Ecology, 2016)
Previously the Reticulated python was recorded by few researchers from Nicobar Islands In 2006, four individuals were observed, but there was no more information added in their literature about sightings in Great Nicobar Island. Pythons were considered as an uncommon and rare encountered species in India also to the Nicobar Islands. Pythons considered relatively rare appearance to have declined due to frequent eradication by habitat destruction On 25th August 2013, first individual of reticulated python was caught by the local people at Govind Nagar (Lat: 07° 00.074' N, Long: 093° 54.128' E, Altitude at 49.4 meter) in Great Nicobar Island The second one was rescued on 31st August 2013 in the same area by the local people. Both the recovered individuals were appeared as juvenile. Investigations on population census of this threatened species and their habitat have been felt from the present incidences. ECOPRINT 22: 50-55, 2015